Forest fires in the Polissiaand their impact on the environment - Didenko, P.V.; Ustymenko, V.I.; Bakay, B. Ya. (Forestry, Forest, Paper and Woodworking Industry, 2019)
It has been established that fire is an element of many forest ecosystems, as it shapes their ecological processes, determines the species composition of the stand and affects the structure of the forest landscape and surrounding areas. The main feature of forest fires is that they have a negative impact on biodiversity and vegetation, create significant carbon emissions, emit smoke, which causes a number of allergic diseases and affects human health, and in many cases causes death and material values. It has been established that climate change can change a number of factors, which in turn will affect the occurrence of fire, the presence of a burning object and the combustible properties of wood. The purpose of this article is to identify probable threats and establish the impact of forest fires on the forest ecosystem, to identify the impact of climate variability and change on forest fires, forest fuels and the likelihood of fires in the natural zone of Ukrainian Polissya. Tools used to assess the dynamics of forest fires and the impact of climate change include: statistics, results of actual surveys of fires, remote sensing, global models of forest vegetation and landscape, integrated models of fire and plant systems, fire risk assessment systems for forest ecosystems, empirical models and models of fire behavior. This article summarizes the results of research both on the fact of using a separate tool and on the basis of their interaction in terms of their characteristics, spatial and temporal resolution, limitations and applicability of results for the forest ecosystem of the Ukrainian Polissya zone. Based on a detailed analysis of materials obtained using various tools, as well as information from open sources, the trend is that the number of fires is growing rapidly and is accompanied by irreparable economic and environmental damage. As a result, there is an awareness of the large-scale negative consequences of forest fires and the reasons that led to them.